Secure Server Authentication Using Graphical and Session Password - Bhosale, Smruti; Botre, Shradha; Chandnani, Gayatri; Kamble, Nikita (International Journal of Computer Sciences and Engineering, 2025)
With today’s technology enhancement, it is possible to store your whole life on your hard drive. But at the same time it increases the risk of information theft. Human generally create passwords that are easy to remember. There are many techniques used to crack passwords like Eves dropping, shoulder surfing, social engineering, etc. To make hacking difficult, we should find out techniques that will increase the security level. So this paper proposes a combination of textual session password and graphical passwords. Session passwords enhance security as they are valid only for certain period of time. Graphical passwords on the other hand are easy to memorize and are better resistant to hacking. Algorithms like Pair based algorithm and Cued Click Point algorithm are used to facilitate the combination.